Understanding a Host–Guest Model System through 129Xe NMR Spectroscopic Experiments and Theoretical Studies1. (22nd July 2014) - Dubost, Emmanuelle; Dognon, Jean‐Pierre; Rousseau, Bernard; Milanole, Gaëlle; Dugave, Christophe; Boulard, Yves; Léonce, Estelle; Boutin, Céline; Berthault, Patrick
Abstract Gaining an understanding of the nature of host–guest interactions in supramolecular complexes involving heavy atoms is a difficult task. Described herein is a robust simulation method applied to complexes between xenon and members of a cryptophane family. The calculated chemical shift of xenon caged in a H2O2 probe, as modeled by quantum chemistry with complementary‐orbital, topological, and energy‐decomposition analyses, is in excellent agreement with that observed in hyperpolarized 129Xe NMR spectra. This approach can be extended to other van der Waals complexes involving heavy atoms.